A música como ciência na obra quinhentista de Vincenzo Galilei - Bromberg, Carla (2009)
Vincenzo Galilei (1520?-1590) was born at Santa Maria a Monte, a small city near Florence. He was a music-theorist, a lutenist and a teacher. He was sent to Venice to start theoretical studies with Gioseffo Zarlino and interested in the studies of ancient texts, he was helped by the philologist Girolamo Mei. Galilei had basically two main goals. The first was to clarify, what he called misunderstood facts of the history of music and the second was to restore music to its original place among the sciences. Therefore he explored the nature of ancient music in a very detailed and systematic fashion and provided novelties based mostly on the results of his investigative method. In experimenting with different materials, cotton, metal, wood, etc., combined into different shapes, Galilei showed to take matter into account to know how it affects the behavior of the instruments. Despite the fact that Music was based on the concept of number, and that most of the musical theorists of the sixteenth century were not interested in the physical nature of sound or in the materials that produce it, Vincenzo Galilei succeeded to provide to Music a new basis, named sound